Platelet-albumin-bilirubin versus albumin–bilirubin as a predictor of long-term survival for hepatitis B-Induced hepatocellular carcinoma after hepatic resection - Haojie Yang; Shuang Shen; Yuting Yang; Houping Zhou; Bangde Xiang (BMC Cancer)
Abstract Background The Child–Pugh (CP) score is widely used to evaluate the severity of liver dysfunction in patients with hepatocellular carcinoma (HCC). Recently, both the albumin-bilirubin (ALBI) and platelet-albumin-bilirubin (PALBI) grade have been raised to be objective measurement indexes of liver function which can sufficiently stratify HCC patient survival. In this study, we aim to compare the ability of albumin-bilirubin (ALBI) and platelet-albumin-bilirubin (PALBI) grade to predict outcomes in hepatitis B-Induced HCC after liver resection with curative intent. Methods Between April 2013 and April 2023, 1005 consecutive hepatitis B-Induced HCC patients who underwent liver resection were included in this study. The performance of PALBI and ALBI score in predicting long-term survival was evaluated. Results The area under the ROC curve (AUC) of the PALBI(AUC:0.618) for predicting long-term survival was greater than that of the ALBI(AUC:0.522). In the multivariate analysis for OS, both the ALBI (HR: 1.246 95%CI: 1.029–1.508 P = 0.024) and PALBI (HR: 1.207 95%CI: 1.049–1.388 P = 0.009) scores were identified as independent predictors of OS in HCC patients. In the univariate analysis for DFS, the PALBI grade was also significantly associated with poor DFS (P = 0.041). In contrast, the ALBI grade was not found to be significantly associated with poor DFS (P = 0.414). Subgroup analysis also showed, among patients across each BCLC stage, the group with ALBI grade 1 had DFS similar to that of the group with ALBI grade 2 (both P > 0.05). However, the PALBI grade can differentiate each BCLC stages into three prognostic groups (all P < 0.05). Conclusion Compared to ALBI grade, the PALBI grade is more clinically feasible and has better prognostic ability regardless of the grade of BCLC stage.